Uji Aktivitas Antibakteri Ekstrak Daun Kopasanda (Chromolaena odorata L.) Terhadap Bakteri Staphylococcus epidermidis - Halid, Musparlin; Hardani (Pharmaceutical and Traditional Medicine, 2022)
Plants that can be used as antibacterial drugs are kopasanda leaves. Traditionally, the leaves of Kopasanda (Chromolaena odorata L.) have been used in wound healing to treat sore throat, malaria medicine, headache, antidiarrheal, and antiplasmodial astringent, antihypertensive and anti-inflammatory. This study aims to determine the antibacterial effectiveness of Kopasanda leaves (Chromolaena odorata L.) against Staphylococcus epidermidis bacteria. This study used a true experimental research method that aims to determine a symptom that arises from the effect of the antibacterial effectiveness of Kopasanda leaf extract (Chromolaena odorata L.) against Staphylococcus epidermidis bacteria. The population in this study is the kopasanda plant. The sample used in this study was kopasanda leaves. While the research instrument uses the results of laboratory tests. Based on the research results, kopasanda leaf extract (Chromolaena odorata L.) has antibacterial activity against Staphylococcus epidermidis. The most effective concentration is at a concentration of 100% with an inhibition zone diameter of 12.17 mm so it is included in the category of strong antibacterial activity